Christian Dior - Cullen, Oriole; Burks, Connie Karol ca. 20. Jh (V&A Publishing, 2019)
Capturing the highlights of the major Victoria and Albert Museum exhibition, Christian Dior: Designer of Dreams, this stunning souvenir celebrates the House of Dior from its foundation in 1947 to the present day. Haute-couture gowns by Christian Dior and the illustrious creative directors who followed him -Yves Saint Laurent, Marc Bohan, Gianfranco Ferre, John Galliano, Bill Gaytten, Raf Simons and Maria Grazia Chiuri-are showcased here, each described by Oriole Cullen and atmospherically photographed by Laziz Hamani. Exhibition: Victoria & Albert Museum, London, UK (02.02.-14.07.2019)
"First published by V&A Publishing to accompany the exhibition "Christian Dior: designer of dreams" on view from 2 February to 14 July 2019 at Victoria and Albert Museum, South Kensington, London SW7 2RL"
Keywords: Dior, Christian -- 1905-1957; Geschichte; Mode; Großbritannien; Ausstellungskatalog -- Victoria and Albert Museum -- 02.02.2019-14.07.2019 -- London; Bildband